Large, loyal, lingering? An analysis of online overseas audiences for UK news brands - Thurman, Neil and Hensmann, Thiemo and Fletcher, Richard (Journalism, 2021)
Amidst the financial crisis affecting UK newspapers, one area of optimism is their online overseas audiences. These foreign visitors often outnumber their domestic equivalents, and some newspapers have made the ‘long-distance’ market a key component of their commercial strategies. Overseas news audiences are, however, under-researched, an omission this study aims to help remedy via an investigation into the audiences for 7 UK newspaper brands (and a public-service broadcaster) across 10 countries using data from a leading source of Internet audience measurement, Comscore. The study uses an innovative, multidimensional model (derived from work by Zheng et al.) to analyse audience engagement across the dimensions of visibility, popularity, depth, loyalty and stickiness. The results reveal that there are significant differences in how audiences behave from country to country, dependent on language and culture. The study has implications for how news organizations serve their overseas audiences and suggests new directions for research into audiences for globalized online journalism.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDY0ODg0OTE5ODkyNDEx